Autotaxin upregulated by STAT3 activation contributes to invasion in pancreatic neuroendocrine neoplasms - Yang, Linfei; Yu, Xiao; Yang, Yongchao (Endocrine Connections, 2018)
Although the upregulation of autotaxin (ATX) is associated with many solid tumours, its role in pancreatic neuroendocrine neoplasms (pNEN) has not been well elucidated. The expression of ATX in pNEN tissues and pNEN cell line BON1 was analysed by Western blot, PCR and immunocytochemistry upon exposure to interleukin-6 (IL-6). Additionally, pNEN cell line BON1 was transfected with siRNAs against ATX or signal transducer and activator of transcription 3 (STAT3) and assessed by in vitro invasion assays.
Gesehen am 28.04.2020